Analysis of circulating hem-endothelial marker RNA levels in preterm infants - Kuint Jacob; Shuchan-Eisen Irit; Pessach Itai; Metsuyanim Sally; Strauss Tzipora; Dekel Benjamin (BMC, 2009)
Abstract Background Circulating endothelial cells may serve as novel markers of angiogenesis. These include a subset of hem-endothelial progenitor cells that play a vital role in vascular growth and repair. The presence and clinical implications of circulating RNA levels as an expression for hematopoietic and endothelial-specific markers have not been previously evaluated in preterm infants. This study aims to determine circulating RNA levels of hem-endothelial marker genes in peripheral blood of preterm infants and begin to correlate these findings with prenatal complications. Methods Peripheral blood samples from seventeen preterm neonates were analyzed at three consecutive post-delivery time points (day 3-5, 10-15 and 30). Using quantitative reverse transcription-polymerase chain reaction we studied the expression patterns of previously established hem-endothelial-specific progenitor-associated genes (AC133, Tie-2, Flk-1 (VEGFR2) and Scl/Tal1) in association with characteristics of prematurity and preterm morbidity. Results Circulating Tie-2 and SCL/Tal1 RNA levels displayed an inverse correlation to gestational age (GA). We observed significantly elevated Tie-2 levels in preterm infants born to mothers with amnionitis, and in infants with sustained brain echogenicity on brain sonography. Other markers showed similar expression patterns yet we could not demonstrate statistically significant correlations. Conclusion These preliminary findings suggest that circulating RNA levels especially Tie2 and SCL decline with maturation and might relate to some preterm complication. Further prospective follow up of larger cohorts are required to establish this association.